Amino Acid Analysis of Fusion (F) Gene and Prediction of Epitope B-Cell Newcastle Disease Surabaya Isolate As Vaccine Candidate - Rahmawati, Indah Laili; Rantam, Fedik Abdul; Tyasningsih, Wiwik (KnE Life Sciences, 2017)
The aims of this research is to determine pathotype according to composition amino acid cleavage site of F protein, and epitope prediction of F protein from Surabaya isolate. Samples were cloacal swabs of 28 backyard chickens from five wet markets in Surabaya, 9 ND positive isolates from Laboratory of Virology and Immunology Department Microbiology Airlangga University, and also positive LaSota isolates (ATCC). Samples were isolated on the embryonated chicken egg and identified by HA test. The viruses were confirmed as NDV by hemagglutination inhibition assay and RT-PCR with target 687 bp. Prediction of epitope were using online software IEDB. The result of epitope B cell prediction from each isolate showing 11-12 epitope B cell candidates in protein F. Thus, it could be concluded that ND virus which isolated from Surabaya has a chance as immunogen candidate, which can be developed as vaccine candidate. Key words: Newcastle disease, Cleavage site, Fusion protein, Surabaya